2009
DOI: 10.1080/14748460903003626
|View full text |Cite
|
Sign up to set email alerts
|

Threshold practices: becoming a student through academic literacies

Abstract: Student transitions into the university are often conceived of via an apprentice-type model, or as entrance into a 'community of practice'. This paper disputes the applicability of these models to the indeterminate and opaque nature of student experiences of academic writing, and proposes that emotional destabilization and struggles around identity are a normal part of both transitions and writing. With reference to student text/visual journals and in-depth interviews, it argues for extending the notion of 'th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 46 publications
0
60
0
4
Order By: Relevance
“…Many of the junior researchers indicated that they felt that they were somehow 'doing it wrong,' which mirrors the student experience (Gourlay 2009). The more experienced writers seemed less concerned about whether they were doing it the 'right way' and more concerned about what worked for them as individuals -specifically their own strategies for disengaging from other tasks (Murray 2013), and engaging with writing, including starting and finishing (Murray and Moore 2006).…”
Section: Processmentioning
confidence: 99%
“…Many of the junior researchers indicated that they felt that they were somehow 'doing it wrong,' which mirrors the student experience (Gourlay 2009). The more experienced writers seemed less concerned about whether they were doing it the 'right way' and more concerned about what worked for them as individuals -specifically their own strategies for disengaging from other tasks (Murray 2013), and engaging with writing, including starting and finishing (Murray and Moore 2006).…”
Section: Processmentioning
confidence: 99%
“…Becoming academically literate involves not only being aware of the rules and expectations of the academic community, but also being able and willing to follow them. It is well documented that many students, particularly those at the beginning of higher education, find the rules of the academic community daunting and challenging especially if they have had limited prior exposure to academic Discourse (Gourlay, 2009;Ivanič, Edwards, Satchwell, & Smith, 2007;Lea & Street, 1998).…”
Section: Academic Literaciesmentioning
confidence: 99%
“…Many of the studies in this review do not have liminality as their main focus, and some merely offer a description of the concept within the introductory sections of the papers in order to provide a background and context for the primary aim of the study -for example, examining threshold concepts and practices (Meyer and Land 2003, Clouder 2005, Gourlay 2009), professional socialisation (Holland 1999, Clouder 2003, transition into first year in higher education (Palmer et al 2009), transition into first year undergraduate nursing (Andrew et al 2009) and student identity (Field 2012). However, within these studies, the authors often returned to comment further on the possibilities and potential of liminality in their discussion or conclusions, and liminality appears as a conceptual thread within many of the articles.…”
Section: Liminality In the Literature: Clarifying The Conceptmentioning
confidence: 99%
“…7 interpretation of threshold concepts (derived from Meyer and Land), in their case study of social work field education; Wallace (2010) considers threshold concepts in relation to adult literacies, and Gourlay (2009) proposes academic literacies as threshold practices, which would benefit from a "liminality analysis" (p189) in order to better understand the transitions some students may experience in developing their academic writing skills. Hurlock et al (2008) offer the most detailed and illuminating examination of the concept of liminality as applied to professional education in their hermeneutic interpretation of interview and email data gathered over a five month period from Tina, a senior social work student.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%